Gamified interaction and urban regeneration: an analysis of serious game participation in rural architectural transformation and its influential factors - Xiangbin Peng; Junjie Li; Huanchen Tang; Qiong Luo (Journal of Asian Architecture and Building Engineering, 2025)
This study investigates the utilization of serious games in rural public building design and their impact on residents’ contentment with building renovations. It highlights serious games’ role as an interactive medium for education, training, and communication, specifically in enhancing residents’ approval of rural public building designs. Employing the concept of diegesis from narratology, the study develops a structural equation modelling (SEM) by dividing games into intra-diegetic and extra-diegetic components. This model examines the influence of Game Participation (GP) and Learning Participation (LP) in serious games on satisfaction with updated building designs, as well as the direct and indirect impacts of various factors on these dynamics. The research methodology encompassed creating and applying a serious game focused on architectural design, accompanied by thorough quantitative analysis of the gaming process and results. The study tested multiple hypotheses regarding the positive impacts of game interactivity, perceived creativity, immersive experiences, game quality, atmosphere, and environment on GP and LP. Notably, the beneficial effect of game engagement on learning engagement and the significant positive influence of GP and LP on design satisfaction underscore the potential of serious games in improving educational outcomes and satisfaction with building renovations. Additionally, enjoyment was identified as having a substantial positive moderating effect on the relationships between GP and Design Satisfaction (DS) and between LP and DS, underscoring the importance of enhancing the appeal and engagement of serious games in their design. Additionally, as the game advanced, participants increasingly aligned their opinions on various design aspects, particularly emphasizing the importance of integrating natural landscapes as a key environmental consideration in community redevelopment.